2015
DOI: 10.3171/2014.11.jns141970
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative identification of neurosurgery patients with a high risk of in-hospital complications: a prospective cohort of 418 consecutive elective craniotomy patients

Abstract: OBJECT Patients undergoing craniotomy are routinely assessed preoperatively, yet the role of these assessments in predicting outcome is poorly studied. This study aimed to identify preoperative factors predicting in-hospital outcome after cranial neurosurgery. METHODS The study cohort consisted of 418 consecutive adults undergoing elective craniotomy for any intracranial lesion. Apart from the age criteria (≥ 18 years), almost all patients were considered eligible for the study to increase external validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 11 publications
2
30
1
1
Order By: Relevance
“…Of the 83 functionally dependent patients at 30 days, 56 patients already had an mRS score $3 preoperatively. Further subgroup analyses showed that patients with a 30-day mRS score $3, in addition to more often having a preoperative mRS score $3 (P , .001), had higher preoperative ASA scores (P = .02) and Helsinki ASA scores (P = .004), 11 were older (P , .001), had higher Charlson Comorbidity Index score (P = .002) and had a longer hospital LOS (P , .001). This subgroup also had a higher proportion of malignant tumors (55.4% vs 22.8%, P , .001; OR: 4.2, 95% CI: 2.5-7.1) and a lower proportion of benign tumors (18.1% vs 34.1%, P = .006; OR: 0.4, 95% CI: 0.2-0.8).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the 83 functionally dependent patients at 30 days, 56 patients already had an mRS score $3 preoperatively. Further subgroup analyses showed that patients with a 30-day mRS score $3, in addition to more often having a preoperative mRS score $3 (P , .001), had higher preoperative ASA scores (P = .02) and Helsinki ASA scores (P = .004), 11 were older (P , .001), had higher Charlson Comorbidity Index score (P = .002) and had a longer hospital LOS (P , .001). This subgroup also had a higher proportion of malignant tumors (55.4% vs 22.8%, P , .001; OR: 4.2, 95% CI: 2.5-7.1) and a lower proportion of benign tumors (18.1% vs 34.1%, P = .006; OR: 0.4, 95% CI: 0.2-0.8).…”
Section: Discussionmentioning
confidence: 96%
“…The protocol of patient enrollment and exclusion criteria were described in a previous article. 11 In brief, of 551 eligible patients, 85 (15.4%) were excluded due to logistic problems in obtaining informed consent before surgery; 47 (8.5%) refused to participate. One patient withdrew the consent during the study.…”
Section: Study Settingmentioning
confidence: 99%
“…Increased risk of perioperative complications has been reported in surgeries such as brain tumor craniotomy [12][13][14][15][16][17]. Reportedly, the length of hospital day after tumor resection is significantly longer in patients with high ASA scores than in those with low ASA scores [12].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the length of hospital day after tumor resection is significantly longer in patients with high ASA scores than in those with low ASA scores [12]. Reponen et al reported that high ASA scores are associated with increased systemic and infectious complications [17]. A more recent study has confirmed that high ASA scores are one of the independent risk factors for surgical site infection after craniotomy [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation